Impacto na qualidade de vida de pacientes submetidos a revascularização do miocárdio - Boni, Andréia Lima Matos Dal (2013)
The objective of this study is to determine the quality of life in patients undergoing myocardial revascularization; to analyze and compare it before and after the intervention; to compare clinic and sociodemographic variables to aspects of depression and anxiety disturbs at pre and post-operative periods. Seventy-eight patients were interviewed at pre and post-operative time, applying the instruments: The Medical Study 36- item Short- From Health Survey (SF-36), Macnew Heart Disease Health - related Quality of Life Questionnaire MacNew, Depression Inventory Beck e Stait Trait Anxiety inventory (Idate). There was a significant improvement in all aspects of the quality of life, depression and anxiety (p=0,05). The SF-36 physical and social aspects represents the lowest scores (13,46 and 3,03, respectively), as well as the social aspect of Macnew instrument (3,03). The social and global Macnew aspects were positively compared to patients with previous acute myocardial infarction, which demonstrates that the revascularization surgery impacted positively in the patients quality of life